Distribution System of Aci Rice Seeds: An Agribusiness Model in Bangladesh - Tanzim Zerin and Hasan Maksud Chowdhury, Sadia (British Journal of Marketing Studies, 2019)
The aim of this report is to investigate the current distribution system of ACI rice seed and propose an effective distribution model for delivering seeds.  The study collected the demand and truck fare data from ACI seed and analyzed their current distribution system’s shortcomings. After analyzing the process, the study found that distance saving matrix with vehicle scheduling method will be appropriate for the distribution of the rice seeds. The study shows how the method will be applied in distribution system and how it will make positive changes in their logistic system. After working with the data of a full season, the study gives a result of 43.62% decrease in distribution cost which will decrease the major operational cost as well. The result indicates that their current distribution system is ineffective and they have much scope to develop in their distribution sector. ACI seed is recommended to follow this distribution method to increase their operation efficiency.